2021
DOI: 10.12681/mms.25753
|View full text |Cite
|
Sign up to set email alerts
|

Commercial catches and discards composition in the central Tyrrhenian Sea: a multispecies quantitative and qualitative analysis from shallow and deep bottom trawling

Abstract: In the Mediterranean Sea, the catch of bottom trawl fisheries is composed of a complex mix of fish and invertebrates with a considerable amount of discards. Seasonal composition of catches and discards of bottom trawls operating at different depths in the central Tyrrhenian Sea were investigated from October 2014 to October 2015. The mean total catch per unit effort (CPUE) ranged between 30.93±8.43 and 27.52±9.88 kg/h in shallow and deep fishing grounds, respectively. The discarded fraction of the catch was 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…Here, we found a distribution of species read abundances consistent with previous knowledge on demersal fish assemblages in the Mediterranean Sea (Russo et al, 2019). Many of the species most frequently found in landings of bottom trawlers in the central Tyrrhenian Sea (Russo et al, 2016;Tiralongo et al, 2021) were among the most abundant in terms of number of reads in our eDNA metabarcoding data; the European hake (Merluccius merluccius), was the most represented species in both COI and 12S data (Figure 5a Sea (Bradai et al, 2012), was among the most abundant species in both the 12S and the COI datasets, coherently with the available knowledge for the area of study (Sbrana et al, 2022).…”
Section: Ta B L Esupporting
confidence: 89%
See 2 more Smart Citations
“…Here, we found a distribution of species read abundances consistent with previous knowledge on demersal fish assemblages in the Mediterranean Sea (Russo et al, 2019). Many of the species most frequently found in landings of bottom trawlers in the central Tyrrhenian Sea (Russo et al, 2016;Tiralongo et al, 2021) were among the most abundant in terms of number of reads in our eDNA metabarcoding data; the European hake (Merluccius merluccius), was the most represented species in both COI and 12S data (Figure 5a Sea (Bradai et al, 2012), was among the most abundant species in both the 12S and the COI datasets, coherently with the available knowledge for the area of study (Sbrana et al, 2022).…”
Section: Ta B L Esupporting
confidence: 89%
“…Here, we found a distribution of species read abundances consistent with previous knowledge on demersal fish assemblages in the Mediterranean Sea (Russo et al, 2019). Many of the species most frequently found in landings of bottom trawlers in the central Tyrrhenian Sea (Russo et al, 2016; Tiralongo et al, 2021) were among the most abundant in terms of number of reads in our eDNA metabarcoding data; the European hake ( Merluccius merluccius ), was the most represented species in both COI and 12S data (Figure 5a,b). Concerning invertebrates, the giant red shrimp ( Aristaeomorpha foliacea ), the deep water rose shrimp ( Parapenaeus longirostris ), the Norway lobster ( Nephrops norvegicus ) and the blue and red shrimp ( Aristeus antennatus ), key target species of trawlers during spring and summer in the central Tyrrhenian Sea, were all in the 10 top species of Figure 5c.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This research work revealed the first evidence of a detectable genetic structure of the necto-benthic, deep-water G. melastomus populations in the Mediterranean Sea and neighbouring North-East Atlantic areas, whose stocks are potentially affected and impacted by the demersal fishery (Tiralongo et al, 2021). Here, we described the first evidence of a weak albeit detectable genetic structure and the development of a technological tool represented by a panel of cross-specific microsatellite loci which were successful in detecting and measuring species genetic diversity and differentiation of blackmouth catshark over a large, regional geographic scale and a significant number of samples and individuals.…”
Section: Discussionmentioning
confidence: 74%
“…The presence of both shape types in the stomach of M. merluccius and M. barbatus and the lack of statistically significant differences based on the chromatic factor support the idea that microlitter may be ingested non-selectively by these two species, even though a biomagnification origin cannot be excluded. Hake and mullet were chosen as experimental models for a variety of reasons: on one hand they are among the most targeted demersal fish species by the Mediterranean deep-sea fisheries and the two most fished target species in the shallow area of the coastal sector (Sabatella et al, 2017;Tiralongo et al, 2021); on the other, they are regarded as bioindicators in coastal marine ecosystems and display a benthic feeding behavior in part of (juvenile M. merluccius) or throughout their lifespan (M. barbatus) (Carrozzi et al, 2019;Esposito et al, 2014). Moreover, some authors already described the occurrence of MPs in these two species (Atamanalp et al, 2021;Avio et al, 2015;Bellas et al, 2016;Digka et al, 2018;Giani et al, 2019;Mancuso et al, 2019) and MPs were demonstrated to abound in superficial sediments in the study area (Piazzolla et al, 2020).…”
Section: Discussionmentioning
confidence: 99%